(3eONd Edi GdQjGVjGJ GdeGdjI h JWHjbGJgG (B/s - (3HGThjI, dMSf YHO Gddgs ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2011)
(3GdefWb GdQjGVj h CfhGY GdGaJQGVGJ , GdeLehYGJ h GdYdGbGJ h GdJWHjbGJ , GdeJJGdjGJ , GdQjGVjGJ GdeGdjI h GdaGFOI GdHSjWI , GdaGFOI GdeQcHI , GdHQeLI GdNWjIs
Keywords: (3GdQjGVjGJs; (3GdQjGVjGJ(B- (3GdeGdjI GdYGeIs